Public spending and poverty in Mozambique - Heltberg, Rasmus; Simler, Kenneth R.; Tarp, Finn (International Food Policy Research Institute, 2003)
Poverty reduction strategies often highlight public spending to improve health and education, focusing on investments in human capital among poorer members of society. In addition, debt relief programs such as the enhanced Highly Indebted Poor Countries (HIPC) initiative often require increased spending on health and education in return for debt cancellation. Mozambiqueís poverty reduction strategy is closely integrated with the government expenditure program, yet up to now little is known about the extent to which public spending is targeted toward the poor in Mozambique. This paper assesses whether public expenditures on education and health are successful at reaching the poorer segments of the Mozambican population. Standard nonbehavioral benefit-incidence methodology is applied, combining individual client information from survey data with provincial-level data on the cost of service provision. Most of the public services we are able to measure are moderately progressive, although some of the instruments we could not measure are probably less equally distributed. In Mozambique, it appears that regional and gender imbalances in health and education are more significant than income based differences. Nevertheless, increased public expenditures on health and education - such as that related to the HIPC initiative - are likely to have significant poverty-reducing effects.